THE IMPORTANCE OF ISLAMIC EDUCATION FOR EARLY CHILDHOOD IN THE DIGITAL AGE - Imam Tabroni; Irma Mulyani; Rini Purnama Sari (Pimpinan Cabang Muhammadiyah Kramat Jati, 2021)
Education is the first milestone in realizing quality human beings, education must of course start from an early age (Golden age). At that time it was important for parents as the first school for children to educate and guide their children to become a generation of intelligent and noble people. With education, children are also taught about Islamic education, so that children can apply moral values, good manners, and good ethics for daily life.